ans. please

Asked by shobhitdc | 25th May, 2010, 01:02: PM

Expert Answer:

6x2 - 7x - 3 = 0,

x = (7±(49 + 4x6x3))/12 = (7±121)/12 = (7±11)/12 = 18/12 and -3/12 i.e. 3/2  and -1/3.

Hence the roots are 3/2 and - 1/3,

Now,  arranging the quadratic equation in standard form,

x2 - 7x/6 - 3/6 = 0,

the sum of the roots should equal coefficient of x, i.e.  7/6.

3/2 - 1/3 = 7/6            .. verified,

also the product of roots be equal to constant term i.e. - 3/6,

(3/2)(-1/3) = - 3/6          ... verified.

Regards,

Team,

TopperLearning. 

Answered by  | 25th May, 2010, 06:59: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.